2018
DOI: 10.1002/pbc.27062
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of the mTOR inhibitor everolimus in combination with multi‐agent chemotherapy in relapsed childhood acute lymphoblastic leukemia

Abstract: Everolimus combined with four-drug reinduction chemotherapy was generally well tolerated and associated with favorable rates of CR2 and low end-reinduction MRD. The recommended phase 2 dose of everolimus given in combination with a four-drug reinduction is 5 mg/m /day. This promising combination should be further evaluated in a larger patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…However, combination of MTIs with alternative salvage chemotherapy backbones that evoke fewer overlapping metabolic toxicities may increase successful delivery of this therapeutic strategy and reinduction of leukaemia remission. For example, in patients with first ALL relapse, preliminary data from a phase 1 trial combining the oral MTI everolimus with a 4‐drug ALL induction has reported CR2 rates approaching 90% with less severe mucosal and gastrointestinal toxicity than was observed in our trial (Place et al , ).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, combination of MTIs with alternative salvage chemotherapy backbones that evoke fewer overlapping metabolic toxicities may increase successful delivery of this therapeutic strategy and reinduction of leukaemia remission. For example, in patients with first ALL relapse, preliminary data from a phase 1 trial combining the oral MTI everolimus with a 4‐drug ALL induction has reported CR2 rates approaching 90% with less severe mucosal and gastrointestinal toxicity than was observed in our trial (Place et al , ).…”
Section: Discussionmentioning
confidence: 50%
“…The study is based on the hypothesis that the combination of temsirolimus, etoposide and cyclophosphamide will result in less additive toxicity, such as hyperglycaemia, hypertriglyceridaemia and/or poor wound healing. In addition, oral formulations of MTIs, such as everolimus (NCT01523977) are being evaluated (Place et al , ). Furthermore, targeting of more proximal or multiple proteins in the PI3K/mTOR pathway with alternative tyrosine kinase inhibitors may result in greater sustained signalling inhibition and, possibly, to less dependence on conventional cytotoxic chemotherapy to achieve cure (Reismuller et al , ; Tasian et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Fouladi et al reported what to our knowledge is the only previous single‐agent everolimus trial for pediatric patients with solid tumors, in which everolimus administered daily demonstrated tolerability and mTOR pathway signaling inhibition in PBMCs . Sporadic case reports have described everolimus use for patients with pediatric central nervous system tumors, acute lymphoblastic leukemia, kaposiform hemangioendothelioma, and vestibular schwannomas …”
Section: Discussionmentioning
confidence: 99%
“…23 Sporadic case reports have described everolimus use for patients with pediatric central nervous system tumors, acute lymphoblastic leukemia, kaposiform hemangioendothelioma, and vestibular schwannomas. [26][27][28][29] The COG performed a randomized study of temsirolimus as an mTOR inhibitor or bevacizumab combined with cyclophosphamide and vinorelbine (ARST0921; ClinicalTrials.gov identifier NCT01222715), 15 whereas the ADVL0918 trial (ClinicalTrials.gov identifier NCT01141244) 16 added temsirolimus to a regimen of irinotecan and temozolomide. Despite widespread interest in bevacizumab for adult cancers, to the best of our knowledge its development and indications for pediatric oncology remain uncertain, reflecting its somewhat disappointing responses in children.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study enrolling children and adolescents with ALL experiencing a first marrow relapse, RAD001 was tested with the natural alkaloid Vincristine and the GC Prednisone or Doxorubicin in subjects with bone marrow relapse occurring >18 months after first CR. With the four‐drug reinduction chemotherapy, the study reported acceptable tolerance and low end‐reinduction minimal residual disease (MRD) level …”
Section: Targeted Therapymentioning
confidence: 99%